PENGEMBANGAN BUKU PENDAMPING PEMBELAJARAN BAHASA INDONESIA TINGKAT LANJUT UNTUK KELAS XI DI PONDOK PESANTREN ABU HURAIRAH MATARAM - Fitria Ayuningsih; Johan Mahyudi; Syaiful Musaddat (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study aims to develop a supplementary textbook for advanced Indonesian language learning on explanatory texts for 11th-grade students at the Abu Hurairah Islamic Boarding School in Mataram and to determine the suitability of the developed textbook. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through observation and questionnaires and analyzed using descriptive quantitative techniques based on feasibility and practicality percentages. The results showed that the developed supplementary book on explanatory texts was designed in accordance with BSKAP guidelines and equipped with learning materials, assessments, a glossary, and supporting learning features. The validation results from design, material, and language experts reached 97%, 93%, and 93%, respectively, indicating a very feasible category. The practicality test showed positive responses from teachers (99%) and students (95%), indicating that the supplementary book is highly feasible and practical for use in learning activities. Based on these results, the developed learning companion book is deemed suitable and practical for use as supplementary teaching material in Advanced Indonesian Language learning for explanatory text content. ABSTRAK Penelitian ini bertujuan untuk mengembangkan buku pendamping pembelajaran Bahasa Indonesia Tingkat Lanjut pada materi teks eksplanasi untuk peserta didik kelas XI di Pondok Pesantren Abu Hurairah Mataram serta mengetahui tingkat kelayakan buku yang dikembangkan. Penelitian ini merupakan penelitian dan pengembangan (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Data dikumpulkan melalui observasi dan angket, kemudian dianalisis secara deskriptif kuantitatif menggunakan persentase kelayakan dan kepraktisan. Hasil penelitian menunjukkan bahwa buku pendamping teks eksplanasi yang dikembangkan sesuai pedoman BSKAP dan dilengkapi materi, asesmen, glosarium, serta fitur pendukung pembelajaran. Hasil validasi ahli desain, materi, dan bahasa memperoleh persentase berturut-turut 97%, 93%, dan 93% dengan kategori sangat layak. Uji kepraktisan menunjukkan respons guru sebesar 99% dan peserta didik sebesar 95%, sehingga buku pendamping dinyatakan sangat layak dan sangat praktis digunakan dalam pembelajaran. Berdasarkan hasil tersebut, buku pendamping pembelajaran yang dikembangkan dinyatakan layak dan praktis digunakan sebagai bahan ajar pendukung dalam pembelajaran Bahasa Indonesia Tingkat Lanjut pada materi teks eksplanasi.